2003
DOI: 10.1245/aso.2003.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Suppresses NK Activity In Vivo and Promotes Postoperative Tumor Metastasis in Rats

Abstract: PGE(2) is a potent in vivo suppressor of NK activity, and its postoperative release may promote tumor recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
94
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 118 publications
(101 citation statements)
references
References 55 publications
3
94
0
4
Order By: Relevance
“…We used a nonselective b-antagonist (propranolol), as human leukocytes and human tumor cells express both b-1 and b-2 adrenoceptors (50, 51), and as our previous study indicated that the blockade of both receptor systems was more effective than each alone in preventing stress-induced promotion of metastasis (52). Importantly, in the clinical setting of oncologic surgery, the drug regimen used in this study may be even more efficient if initiated a few days before surgery, because etodolac could reduce PGs release by primary tumors (14); propranolol could reduce anxiety (53) and antagonize the excess release of CAs owing to preoperative physiologic and psychologic stress responses (54,55). Together, preoperative use of these drugs can attenuate preoperative suppression of CMI in cancer patients awaiting surgery (10,56).…”
Section: Sectionmentioning
confidence: 64%
See 2 more Smart Citations
“…We used a nonselective b-antagonist (propranolol), as human leukocytes and human tumor cells express both b-1 and b-2 adrenoceptors (50, 51), and as our previous study indicated that the blockade of both receptor systems was more effective than each alone in preventing stress-induced promotion of metastasis (52). Importantly, in the clinical setting of oncologic surgery, the drug regimen used in this study may be even more efficient if initiated a few days before surgery, because etodolac could reduce PGs release by primary tumors (14); propranolol could reduce anxiety (53) and antagonize the excess release of CAs owing to preoperative physiologic and psychologic stress responses (54,55). Together, preoperative use of these drugs can attenuate preoperative suppression of CMI in cancer patients awaiting surgery (10,56).…”
Section: Sectionmentioning
confidence: 64%
“…One possible explanation for this synergism is that during the postoperative period both PG and CA levels are high, and each factor alone can interfere with NKC by activating its membrane receptors on NK cells, which, through the same intracellular mechanisms elevate intracellular cAMP levels and cause suppression of NKC (14,15). Similar mechanisms regulate CTL and NKT activity, and CAs and PGs have analogous immunosuppressive effects on many aspects of CMI (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells differ from conventional  T cells and B cells in that they use numerous activating and inhibitory receptors which can operate independently one from another to trigger or inhibit destruction of target cells [3]. Even if previous reports have demonstrated that PGE 2 is able to suppress the destruction of some tumor cell lines by NK and  T cells [21,23,24], it remains undetermined which receptors are subjected to inhibition by PGE 2 . In this 17 report, using mAbs for redirecting the specific lysis of the mouse FcR + cell line P815, we clearly demonstrate that the major NKR (NKp30, NKp44, NKp46, NKG2D and CD16) and the major  T cell receptors (TCR V9V2, NKG2D and CD16) are all inhibited by PGE 2 through a cAMPmediated PKA type I-dependent mechanism following the binding of PGE2 on EP2 and EP4.…”
Section: Discussionmentioning
confidence: 99%
“…PGE 2 has also been involved in the inhibition of NK and  T cell cytolytic functions [21][22][23][24]. Nevertheless, studies that analyzed the regulation of NK and  T cell functions by PGE 2 only focused on its ability to regulate their cytotoxicity against target cells.…”
Section: Introductionmentioning
confidence: 99%